Changes in Cardiometabolic Risk Factors Before and After Gestational Diabetes: A Prospective Life Course Analysis in CARDIA Women - Catov, Janet M. (Obesity (Silver Spring), 2020)
OBJECTIVE: We hypothesized that both preconception and post-childbearing patterns of cardiometabolic risk factors may be different for women with gestational diabetes (GDM) compared to women without GDM. METHODS: Among 1,302 (51% Black) women in the Coronary Artery Risk Development in Young Adults study with births and followed for 30 years, we evaluated changes in cardiometabolic factors (BMI, waist circumference [WC], lipids, blood pressure) during pre-childbearing (prior to the first post-baseline birth) and post-childbearing periods (after the last birth) by GDM status using piecewise linear mixed-models adjusted for socio-demographics, parity and time-varying covariates. RESULTS: Compared to women who did not develop GDM, weight and WC increases in women who developed GDM (n=152, 12%) were faster (BMI difference +0.12 kg/m(2) per year [p=0.04]; WC difference +0.28 cm per year [p=0.04]) during the pre-childbearing period, accounting for covariates. This translated to an average of 1.3 kg excess weight gain across 4 years among women with subsequent GDM vs. non-GDM births. In contrast, slopes after childbearing did not differ by GDM status nor were there other cardiometabolic differences. CONCLUSIONS: Women with GDM exhibited an increasing pre-pregnancy pattern of weight gain and central adiposity. Absolute post-childbearing weight was also higher in GDM-affected women but the slope of gain after GDM was not.